Immune Complex Formation Is Associated With Loss of Tolerance and an Antibody Response to Both Drug and Target - Kroenke, Mark A.; Barger, Troy E.; Hu, Jenny; Miller, Mieke Jill; Kalenian, Kevin; He, Lidong; Hsu, Hailing; Bartley, Yessenia; Chow, Vincent Fung-Sing; Teixeira dos Santos, Marcia Cristina; Sullivan, Barbara A.; Cheng, Laurence E.; et al. (Frontiers in Immunology, 2021)
AMG 966 is a bi-specific, heteroimmunoglobulin molecule that binds both tumor necrosis factor alpha (TNFa and TNF-like ligand 1A (TL1A). In a first-in-human clinical study in healthy volunteers, AMG 966 elicited anti-drug antibodies (ADA) in 53 of 54 subjects (98.1%), despite a paucity of T cell epitopes observed in T cell assays. ADA were neutralizing and bound to all domains of AMG 966. Development of ADA correlated with loss of exposure. In vitro studies demonstrated that at certain drug-to-target ratios, AMG 966 forms large immune complexes with TNFa and TL1A, partially restoring the ability of the aglycosylated Fc domain to bind FcgRIa and FcgRIIa, leading to the formation of ADA. In addition to ADA against AMG 966, antibodies to endogenous TNFa were also detected in the sera of subjects dosed with AMG 966. This suggests that the formation of immune complexes between a therapeutic and target can cause loss of tolerance and elicit an antibody response against the target.